Systematic Review The Effectiveness of Fibrinolytic Therapy in STEMI Patients - Anindya Widyasari Ekasuci; Laksmi Maharani; Dewi Latifatul Ilma (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2020)
The use of fibrinolytic as a reperfusion therapy for STEMI patients has many benefits, but in its use, it is not yet decided whether fibrinolytic therapy is an effective therapy for STEMI patients. This study aimeds to evaluate and determine the effectiveness of fibrinolytic therapy for STEMI patients through a systematic review method. The selected articles PubMed and Cochrane that fulfilled the keyword search based on PICO (fibrinolytic or thrombolytic, effectiveness or efficacy), and were uploaded from 2010 to 2020 were included in this study. The searching was conducted from 15 May 2020 untill 27 June 2020. From the total of 525 searches displayed, 17 articles were included in the inclusion criteria. Research showed that fibrinolytic with rescue PCI or as adjunctive therapy is an effective therapy in STEMI patients by increasing myocardial perfusion, epicardial flow, ST segment resolution, TIMI score, peak time to troponin reach, and reduce LVEF risk. Fibrinolytic therapy with rescue PCI or as adjunctive therapy is also effective in reducing infarct size and the risk of cardiogenic shock. Fibrinolytic as pharmacoinvasive therapy is an effective therapy for patients with a diagnosis of STEMI.